Impacts of Pervasive Climate Change and Extreme Events on Rocky Intertidal Communities: Evidence From Long-Term Data - Mieszkowska, Nova; Burrows, Michael T.; Hawkins, Stephen J.; Sugden, Heather (Frontiers in Marine Science, 2021)
Annual surveys of the abundance of intertidal invertebrates and macroalgae have been made at between 70 and 100 rocky intertidal time-series sites around the United Kingdom coastline since 2002 under the MarClim project. The data provide a unique opportunity to investigate the impacts of both pervasive climate change and their punctuation by extreme events on intertidal species. After the extreme storm events in the 2013/2014 winter season and the record heatwaves in the summers of 2018 and 2020, MarClim surveys recorded both physical and biological changes to rocky shore habitats. Subsequent surveys reassessed the effects on community structure via analysis of those species that resisted storm damage, those species that returned after the extreme storm events, and species that opportunistically occupied vacant habitat after storm-induced species loss. In addition, biannual storm damage surveys documenting communities recovery were carried out in the spring and winter of each year from 2014 to 2020 at three MarClim sites in north Cornwall (Crackington Haven, Trevone, and St. Ives), which experienced different types of abiotic and biotic damage resulting from these storms. Impacts of heatwaves and cold spells on the abundance of species were determined by regression on frequencies of event per year. Species of invertebrates and macroalgae generally declined in years of more frequent winter cold spells and summer heatwaves, while winter heatwaves and summer cold spells had similar numbers of positive and negative effects across species. Winter warm spells tended to have a more negative effect on cold-affinity species than on warm-affinity species. No abrupt shift was recorded after the 2013/2014 storms. Whilst a short-term change in some species was recorded in quantitative quadrat surveys, the biological communities returned to the long-term species composition and abundance within 2 years. The heatwave events caused sublethal heat damage in macroalgae, evidenced as dried areas of tissue on many individuals, with mortality-induced reductions in the abundance of only a few invertebrate species, recorded in Scotland and southwest England after the heatwave events in 2018 and 2020. MarClim and storm-damage surveys indicate that there have been no sustained impacts from either extreme thermal or storm events across the rocky intertidal communities, and biodiversity has not been significantly altered as a result. The abundance and biogeographical distributions of rocky intertidal species and communities around the United Kingdom are being driven by longer-term, large scale, pervasive change in environmental conditions, with a gradual shift towards dominance of Lusitanian species from the early 2000s in responses to warming of the marine climate.